2020
DOI: 10.1075/ni.18053.pop
|View full text |Cite
|
Sign up to set email alerts
|

A bene placito*

Abstract: Sex work is often interpreted through master narratives that see women as victimized and subjected to stigmas and negative attitudes. This paper offers an insight into narratives that challenge or can be seen as an alternative to these narratives. Data are from a sample of 15 interviews with women who show an interest in sex work, conducted in a netnographic context. While widespread master narratives about sex work tend to revolve around the notion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…All of them were Italian and come from Foggia, a city in the region of Apulia affected by a marked presence of organized crime. 1 The subject selection procedure for this study relied on the notion of deep interest (see Poppi and Sandberg, 2020; Raitanen et al, 2019): the participants were selected for having (1) an interest in considering organized crime as an interesting topic, in both factual and fictional representations (for example films, TV series) and (2) a willingness to consider the possibility of justifying some activities in which organized crime was generally involved.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All of them were Italian and come from Foggia, a city in the region of Apulia affected by a marked presence of organized crime. 1 The subject selection procedure for this study relied on the notion of deep interest (see Poppi and Sandberg, 2020; Raitanen et al, 2019): the participants were selected for having (1) an interest in considering organized crime as an interesting topic, in both factual and fictional representations (for example films, TV series) and (2) a willingness to consider the possibility of justifying some activities in which organized crime was generally involved.…”
Section: Methodsmentioning
confidence: 99%
“…Personal narratives are particularly relevant on a personal level because their content is more likely to reflect individual differences in personality characteristics and life experiences (McLean et al, 2007). In this regard, personal narratives are thematically based (Poppi et al, 2018; Poppi and Sandberg, 2020) and shape the ways in which individuals attend to, and feel about, events and social phenomena (Ochs and Capps, 1996).…”
Section: Narrative Criminology and Interactional Fantasizingmentioning
confidence: 99%
See 2 more Smart Citations
“…No one has used narrative criminology to study incels, and only a few have used the framework to study sexual offenses more generally. However, research within narrative criminology has shown how women sex workers experience gender violence, intersecting forms of subjugation and oppression (Boonzaier 2019), and how alternative narratives can instigate and sustain sex work (Poppi and Sandberg 2020). Narrative criminology has also highlighted the importance of stories in managing shame for sex offenders who try to make sense of themselves and their victims (Ievins 2019) while attempting to habilitate themselves after participating in treatment programs for sexual offenders in prison (Victor and Waldram 2015).…”
Section: Narrative Criminology Cultural Criminology and Symbolic Boun...mentioning
confidence: 99%